Efficacy and Safety of Iris-Claw and Scleral Fixated Intraocular Lens in Pediatric Ectopia Lentis : A Systematic Review: Oral Presentation - Observational Study - Resident - SORAYA, SITI HALIDA Z.; Estu, Dian (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Ectopia lentis is a condition that involves displacement of the crystalline lens because of weakened or damaged zonules. Surgical intervention is indicated in cases of poor best corrected visual acuity (BCVA) and progressive severity of subluxation. This systematic review aims to elucidate current evidence regarding the efficacy and safety of iris-claw and scleral-fixated intraocular lenses (IOLs) to treat children with ectopia lentis. Methods : A comprehensive search from multiple electronic databases such as PubMed, Cochrane Library, ProQuest, Scopus, EBSCO, Wiley, and Embase within the last ten years of publication. All seventeen studies matched with studies’ criteria were included in this review and assessed with eligibility assessment tools. The outcomes extracted and compared were BCVA, endothelial cell density, postoperative complications, IOL stability, and intraocular pressure (IOP). Results : Seventeen studies were included in this review; three observational studies, nine retrospective studies and five interventional studies in which majority have a low risk of bias. Significant improvement of post-operative BCVA on both IOLs. The most frequent complications found on ICIOL was pupillary ovalization, while SCIOL was eye infection. Endothelial cell loss was higher in SCIOL, and both IOL showed no significant difference (p > 0,05) in terms of the post-operative IOP. Dislocation of IOL more frequently found on ICIOL. However, ICIOL much more preferred due to less manipulation and duration of surgery. Conclusion : ICIOL and SFIOL were both effective and safe for treating pediatric ectopia lentis. There was no superiority in which technique is better, technique varied according to each surgeon's preference.